2007
DOI: 10.1038/sj.ejcn.1602614
|View full text |Cite
|
Sign up to set email alerts
|

Capturing the onset of the common cold and its effects on iron absorption

Abstract: Hypoferremia is a well-known response to infections and inflammatory disorders. It seems to be managed by the key mediator of iron kinetics, hepcidin. There are several studies on induced-acute phase reactions. However, to our best knowledge there are no previous published reports on the outbreak of a common cold and its initial effect on iron kinetics. The objective of this case report is to describe such an observation. From an apparently healthy state in the morning we observed, in a 28-year-old male, every… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Limited research data from adult populations attempt to elucidate the role of hepcidin in the common cold, iron metabolism disorders, chronic kidney disease, chronic hepatitis C and kidney transplant recipients [25-27]. In an adult patient population study group, hepcidin was demonstrated as a potentially useful marker that reflects the degree of billiary inflammation in cholecystitis and primary sclerosing cholangitis (PSC) - associated bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…Limited research data from adult populations attempt to elucidate the role of hepcidin in the common cold, iron metabolism disorders, chronic kidney disease, chronic hepatitis C and kidney transplant recipients [25-27]. In an adult patient population study group, hepcidin was demonstrated as a potentially useful marker that reflects the degree of billiary inflammation in cholecystitis and primary sclerosing cholangitis (PSC) - associated bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of such a feedback mechanism remains speculative, there is clear evidence for each step in this process. Significantly elevated IL-6 levels have been measured in South American hemorrhagic fevers [27], and increased IL-6 and hepcidin is observed with several other viral infections, for example in individuals acutely infected with common cold viruses or chronically infected with hepatitis C virus [9,33]. The links between IL-6 levels, hepcidin concentration, hypoferremia, and TfR1 upregulation have also been established [25].…”
Section: Iron Sequestration Tfr1 Expression and Arenaviral Hemorrhamentioning
confidence: 95%
“…Neither could they take any dietary supplements (including iron) or use any probiotic containing products during the study or within two weeks prior to the study. Exclusion criteria also included infection / inflammation since an activated acute-phase reaction can cause extensive changes in body iron metabolism, including reduced iron absorption [ 44 – 46 ]. In the event of an activated acute-phase response, S-ferritin is falsely elevated [ 47 ].…”
Section: Ethicsmentioning
confidence: 99%